Pengembangan Model Manajemen Bimbingan dan Konseling di Sekolah Dasar - Jarkawi Jarkawi; Yulizar Abidarda (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study is to produce guidance and counseling management products in elementary schools by adjusting the characteristics of students in swampland, where the development component focuses on (1) planning, (2) organizing, (3) implementing, (4) evaluating, and (5) follow-up. The methodology used by the researcher is research and development, by adopting four of the 10 stages of Borg and Gall, including the following: (1) preliminary study. (2) hypothetical development, (3) hypothetical model review, (4) revision. The results of this study are: (1) guidance and counseling services in elementary schools have not been ideal in their implementation, (2) compiled and validated a prototype of guidance and counseling management in elementary schools in swampy areas. The conclusion obtained from this study is that the guidance and counseling management model in elementary schools in swampy areas has been tested, (1) considering that this model has been validated by academics with a background in guidance and counseling education, and validated by school teacher practitioners. which will later carry out guidance and counseling services at the schools where they work.